Development of Digital Ethno-STEM Teaching Materials on Renewable Energy for Patriotism - Maslichah, Dina; Rusilowati, Ani; Astuti, Budi; Hartono, Hartono; Linuwih, Suharto; Sugianto, Sugianto; Widiyatmoko, Arif; Sutikno, Sutikno (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2025)
This research produced a product in the form of ethno-STEM-based digital teaching materials on renewable energy. The research method used was Research and Development (R&D) with the Analyze, Design, Development, Implementation, and Evaluation (ADDIE) development model. The development stage was limited to the development stage because this study focused on the content validity and design of ethno-STEM-based digital teaching materials on renewable energy. The purpose of this study was to produce teaching materials that were feasible and effective in fostering a love for the homeland in students. The results showed that the ethno-STEM-based digital teaching materials were developed in accordance with BSNP standards and digital media. The characteristics of the digital teaching materials produced lie in the holistic integration of the bamboo spinning top culture in the STEM approach. The material validity test results for the teaching materials obtained a score of 96.35%, and the media validity obtained a score of 97.41%. Thus, it can be stated that ethno-STEM teaching materials are suitable for use in learning. The teaching materials developed not only meet technical requirements but also have pedagogical potential in supporting physics learning that fosters a sense of patriotism through the integration of regional cultural potential. However, this study is limited to the development stage, so further studies are needed to test the effectiveness of teaching materials in fostering a sense of patriotism in students.